(untitled) (Journal of the College of Basic Education, 2022)
The research concerned (overcrowding and its reflection on the performance of the industrial product) in explaining the concept of overcrowding. The research aims to determine the role of overcrowding and its reflection on the performance of the industrial product. The importance of this study stems from the fact that it is the first to deal with this field. Therefore, it is the first building block in building a knowledge foundation and a theoretical base that deals with overcrowding in industrial products. The study consisted of five chapters. The first chapter included the research problem, its importance and objectives. Its limits and terminology, either the second chapter included the theoretical framework and previous studies, while the third chapter included research procedures and methodology